THE ROLE OF THE DIMENSIONS OF THE TARGET COST APPROACH IN PRICING BANKING SERVICES FOR COMMERCIAL BANKS TO ACHIEVE A SUSTAINABLE COMPETITIVE ADVANTAGE - Raheem Abed Mohammed (American Journals, 2023)
The aim of the study is to determine how the use of the target cost method for pricing banking services affects the ability to maintain a sustainable competitive advantage. While the study focused on finding a solution to the issue of the multiplicity and diversity of these services provided to customers, as well as increasing the use of technology through which services are provided, which exposes commercial banks to high competition in the banking services market. To achieve the objectives of the study, a questionnaire consisting of several paragraphs was designed, addressed to a group of (80) clients dealing in the banking sector. As for the study sample, (10) commercial banks operating in this financial sector were selected, and many statistical methods were used to achieve the objectives of the study. After conducting the study analysis process and its hypotheses, the study reached a number of results, the most important of which is that most commercial banks apply the target cost method. There is a need to adopt the target cost approach in pricing in order to ensure the survival and continuity of the sustainable competitive advantage, as all of the paragraphs that measure the competitive advantage in commercial banks obtained high averages. This is an indication that the pricing of services in these commercial banks is done through the target cost method, in addition to the development of cost systems that effectively contribute to the decision-making process. The study reached a number of recommendations, the most important of which is the need for commercial banks to expand the application of the target cost approach to achieve benefits, benefits and competitiveness in light of global economic and technological developments, as well as working to educate banks about the importance of this approach and its advantages through holding seminars and training courses by the Central Bank. Aware of the importance of using target costing in this field, the study also recommended that commercial banks increase the use of the target costing approach to achieve the advantage of sustainable competition.
Keywords: Target costing, pricing of banking services, sustainable, competitive, advantage.